Effective cleaning process and its influence on surface roughness in anodic bonding for semiconductor device packaging. (March 2015) - Joyce, Robin; Singh, Kulwant; Varghese, Soney; Akhtar, Jamil
Abstract: Wafer cleanliness and surface roughness play a paramount role in an anodic bonding process. Impurities and the roughness on the wafer surface result in unbonded areas which lead to fringes and Newton׳s rings. With an augment in surface roughness, lesser area will be in stroke thus making more pressure and voltage to be applied onto the wafers for better bonding. Eventually it became mandatory to choose the best cleaning process for the bonding technology that can substantially reduce the impurities and surface roughness. In this paper, we investigate the bonding of silicon/oxidized silicon on Pyrex (CORNING 7740) glass with respect to surface roughness and cleanliness of the wafers by performing three renowned cleaning processes such as degreasing, piranha, RCA 1& 2 (SC‐Standard Cleaning 1 and 2) and found that RCA compromises the best between the roughness and cleanliness. Studies were also extended to find out the effects of applied voltage and load on the bonded surface. It was observed for samples cleaned with RCA, an increase of 45% in maximum current and decrease of 75% in total bonding time with the applied load and voltage among all the cleaning techniques used. Three dimensional structures for pressure sensor application were successfully bonded by selecting the appropriate load and cleaning process. Atomic force microscopy analysis was done to investigate the surface roughness on silicon/oxidized silicon and Pyrex glass for different cleaning processes. Scanning electron microscopy and optical imaging were performed on the interface for the surface integrity of the bonded samples.